HAK-HAK NORMATIF PEKERJA KARENA PHK DENGAN ALASAN EFISIENSI SEBELUM DAN SESUDAH UNDANG-UNDANG TENTANG CIPTA KERJA: Normative Rights of Workers Due to Laid off Efficiency Before and After Act on Job Creation - Sari, Linda Ganetha; Adityaningrum, Narita (AMICUS CURIAE, 2025)
Normative rights are fundamental rights that must be owned by a worker/laborer in an employment relationship. Regarding the case in the decision to analyze the comparison of normative rights to be obtained by workers referring to the Job Creation Law. The problem identification is: what are the normative rights of layoffs before and after the enactment of Law No. 11/2020 related to District Court Decision Number: 363/Pdt.Sus-PHI/2022/PN.Jkt.Pst and Decision Number 18/Pdt.Sus-PHI/2019/PN.Jap?  The result of the discussion is that layoffs for efficiency reasons are not allowed because the Constitutional Court's decision is a reinforcement that companies can only choose a way to carry out layoffs because the company is permanently closed and efficiency cannot be used as a strong reason to lay off workers/laborers and the legal consequences of layoffs in the decision are null and void and normative rights must be fulfilled by employers/employers who carry out layoffs, in the form of severance pay, long service pay, compensation pay must be received by workers/laborers as stated in the Manpower Law and Law No. 11/2020 concerning Job Creation.